2009
DOI: 10.1002/crat.200800315
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of Nd doped gadolinium gallium garnet nanopowders and crystals

Abstract: The structural and optical features of gallium gadolinium garnet (GGG) nanopowders doped with neodymium were investigated. Nanopowders of GGG:Nd were prepared by modified sol-gel method using acetic acid as complexing agent. This way permitted to incorporate large amounts of dopant (up to 10 %) without destroying garnet structure. Small single crystals of Nd:GGG were grown by a µ-pulling down method and spectroscopic features of nanopowders and their single crystal counterparts were compared. It has concluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, in the literature one can nd examples in which the experimental lifetimes for an electronic level of a RE 3+ ion introduced as dopant in a bulk matrix and its equivalent nanoparticle have been compared, and the radiative probabilities have been considered approximately equal. 34,35 For example, Lipińska et al 34 have calculated the lifetime of the 4 F 3/2 level of Nd 3+ ions in Gd 3 Ga 5 O 12 (GGG) nanopowder and crystal garnets, and they found comparable results between them, or V. I. Zhekov et al 35 in Y 3 Al 5 O 12 (YAG) crystal doped with Er 3+ ions have observed a similar behavior for the 4 I 13/2 / 4 I 15/2 transition. Although it Fig.…”
Section: Cb Temperature Dependence Of the Stokes Luminescence Of Er 3...mentioning
confidence: 99%
“…However, in the literature one can nd examples in which the experimental lifetimes for an electronic level of a RE 3+ ion introduced as dopant in a bulk matrix and its equivalent nanoparticle have been compared, and the radiative probabilities have been considered approximately equal. 34,35 For example, Lipińska et al 34 have calculated the lifetime of the 4 F 3/2 level of Nd 3+ ions in Gd 3 Ga 5 O 12 (GGG) nanopowder and crystal garnets, and they found comparable results between them, or V. I. Zhekov et al 35 in Y 3 Al 5 O 12 (YAG) crystal doped with Er 3+ ions have observed a similar behavior for the 4 I 13/2 / 4 I 15/2 transition. Although it Fig.…”
Section: Cb Temperature Dependence Of the Stokes Luminescence Of Er 3...mentioning
confidence: 99%
“…This indicates substitution of gadolinium by neodymium. The lattice parameter increases because neodymium ion has bigger size than gadolinium ion 22 . Diffused reflectance spectra of Nd:GGG in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They have decreased the evaporation of molten Ga 2 O 3 by means of 10% CO 2 instead of O 2 in the atmosphere. The oxygen partial pressure increases with temperature; consequently, oxidation of iridium (Ir) crucible decreases [14]. Jia et al [15] have taken the polycrystalline Nd:GGG as starting material to produce the large size Nd:GGG crystal.…”
Section: Introductionmentioning
confidence: 99%